1997
DOI: 10.1074/jbc.272.17.11035
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-dependent Activation of the Leukocyte NADPH Oxidase in a Cell-free System

Abstract: The leukocyte NADPH oxidase catalyzes the 1-electron reduction of oxygen to O 2 ؊ at the expense of NADPH: 2 O 2 ؉ NADPH 3 2 O 2 ؊ ؉ NADP ؉ ؉ H ؉ . The oxidase is dormant in resting cells but acquires activity when the cells are stimulated with a suitable agent. Activation in whole cells is accompanied by extensive phosphorylation of p47 PHOX, an oxidase subunit located in the cytosol of resting cells that during oxidase activation migrates to the plasma membrane to complex with cytochrome b 558 , an oxidase-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 58 publications
1
44
0
1
Order By: Relevance
“…The effect of the ⑀PKC inhibitor peptide to abolish both an increase in DHE fluorescence and a decrease in I p supports the functional role of PKC activation. PKC-dependent phosphorylation of the cytosolic NADPH oxidase subunit p47 phox induces its translocation to the membranous p22 phox subunit that is required for activation of NADPH oxidase (24). Consistent with NADPH oxidase activation, forskolin induced an increase in co-immunoprecipitation of p47 phox with p22 phox , and apocynin abolished the forskolininduced increase in DHE fluorescence.…”
Section: Namentioning
confidence: 50%
“…The effect of the ⑀PKC inhibitor peptide to abolish both an increase in DHE fluorescence and a decrease in I p supports the functional role of PKC activation. PKC-dependent phosphorylation of the cytosolic NADPH oxidase subunit p47 phox induces its translocation to the membranous p22 phox subunit that is required for activation of NADPH oxidase (24). Consistent with NADPH oxidase activation, forskolin induced an increase in co-immunoprecipitation of p47 phox with p22 phox , and apocynin abolished the forskolininduced increase in DHE fluorescence.…”
Section: Namentioning
confidence: 50%
“…In resting phagocytes, the NADPH oxidase is in a dormant state, but exposure of the cell to any of a variety of stimuli can activate the enzyme, causing it to release large amounts of O 2 Ϫ by reducing oxygen at the expense of NADPH. The oxidase is activated by the phosphorylation of one of its cytosolic subunits, p47 PHOX , on particular serines (1). In whole cells, the stimulation of an appropriate receptor activates PKC and phosphatidylinositol 3-kinase (PI3-kinase) (2)(3)(4).…”
mentioning
confidence: 99%
“…Recently, the phosphorylation of p67Phox which exists in a complex with p47Phox in the cytosol, has been shown to occur upon stimulation in a PKC-dependent and PKC-independent manner (35). Furthermore, Park et al (13) showed that, in a protein kinase-dependent cell-free system, the initial step of the activation process was taking place in the membrane and required the action of one or more kinases. This step might also exist in intact cells and implicate the phosphorylation upon stimulation of the two subunits of the flavocytochrome b that was reported several years ago by Segal and co-workers (36,37 PMN with these inhibitors induced an increase in the rate and extent of the respiratory burst stimulated by the chemotactic peptide f-Met-Leu-Phe (fMLP) (14,39).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, p47Phox has consistently been shown to become extensively phosphorylated on multiple serine residues (8)(9)(10)(11). Several studies demonstrated that this multiple phosphorylation is an essential step in intact PMN and is required for translocation of this protein and for activation of the respiratory burst oxidase but is dispensable in the cell-free system (12,13). Although many studies have focused on the mechanisms of activation, less is known about the turnoff mechanisms.…”
Section: Introductionmentioning
confidence: 99%